PROCEDURE FOR PUTTING BUSINESS CONTRACTS IN THE TRANSFER OF TECHNOLOGIES - Загрішева, Надія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article deals with the procedure for concluding an economic contract and identifying the features of its conclusion for the sphere of technology transfer. Results: consent, which forms the basis of any contract, is understood as a coincident at a certain point in time, the mutual recognition of the will, aimed at satisfying the legal result of the property nature. Contractual relationship between the parties begins with the stage of negotiations on the conclusion of the contract. The contract is the will of the parties, which in the future transforms into action, aimed at acquiring, changing or terminating rights and obligations. The legislator, establishing a general procedure for the conclusion of economic contracts, notes the existence of additional conditions for the conclusion of economic contracts for certain categories of property. It is suggested that the conclusion of a commercial contract is the registration of contractual relations in the form of a mutually agreed will of the parties, preceded by a certain sequence of actions in the form of will expressions. At the same time during the alienation of property rights to technology under the contract: the moment of alienation of property rights to technology is considered the moment of the will of the parties, which is confirmed by the actual conclusion of the contract, and the subject receiving the right to technology acquires ownership of the technology, of all its constituent parts and property in which technology is objectified simultaneously.